Menentukan Tingkat Kelayakan Tanah Lempung Untuk Menyalurka Beban Kontruksi (Determining the Feasibility Level of Clay for Distributing Construction Loads) - Ricky Putra Ardianto; Agata Iwan Candra; Ogest Tegar Widyakrama; Rahmat Heru Supriyo; Arif Rivianto (Universitas Batanghari Jambi, 2023)
In the course of the development of the world of civil construction, soil is a building material that can function as the foundation of a building structure. Clay soil is a type of soft soil with fine grain characteristics. The soil has a shrinkage property where when exposed to water it will expand according to the amount of water absorbed, but when it is dry it will shrink to its original dimensions with non-directional compaction. The consistency of clay soil does not support the safety of the building it supports. In constructing a construction, it is necessary to plan a sturdy and strong soil structure to prevent slip failure (clayey & longitudinal). The soil that often experiences problems in the construction of civil construction is clay. Therefore, a Direct Shear test was carried out at the Kadiri University Civil Engineering Laboratory. The results of this study obtained the value of the soil shear strength parameters. The direct shear strength test aims to determine the feasibility of the soil to accept construction loads, obtain parameters of the shear strength of disturbed soil or unconsolidated and undisturbed undisturbed soil. The shear strength test of the soil is carried out to determine the strength of the soil against the displacement that occurs in the soil. Based on the results of the direct shear strength test, the cohesion value was 0.330 and the shear angle value was 2.929. This value indicates that this soil is unstable, prone to landslides and is not feasible to carry construction loads